Moral distress, ethical climate, and compassion fatigue among oncology nurses: the mediating role of moral distress - Akbar Zare-Kaseb; Fariba Borhani; Abbas Abbaszadeh; Amir Mohamad Nazari (BMC Nursing)
Abstract Background Oncology nurses have a vital role in providing care for individuals with cancer. Ethical dilemmas arise for oncology nurses caring for these patients. Nurses experience moral distress when work conflicts with personal beliefs, leading to inappropriate responses or uncertainty about ethics. The ethical climate might influence nurses' response to moral distress. Moral distress in nurses can lead to work-related stressors like compassion fatigue. Research objectives This study examined the relationship between moral distress, ethical climate, and compassion fatigue in oncology nursing. Moreover, the role of moral distress as a mediator in the link between ethical climate and compassion fatigue was examined. Method A descriptive correlational design was recruited. One hundred twenty-two participants were recruited using the convenience sampling method. The study data were collected using a demographic information form, Corley's Moral Distress Questionnaire, Revised Victor and Cullen's Ethical Climate Questionnaire, and the Professional Quality of Life questionnaire. The Ethics Research Center of Shahid Beheshti University of Medical Sciences approved the study. Findings The overall moral distress, compassion fatigue, and ethical climate mean scores were 125.54 ± 37.50, 31.50 ± 9.23, and 49.03 ± 7.49, respectively. The analysis showed that among the dimensions of ethical climate (including egoism, benevolence and principled climate), egoism directly (p=0.03) and indirectly (p<0.001) and benevolence indirectly (p<0.001) (through moral distress) were significantly related to compassion fatigue. The principled ethical climate did not show any direct or indirect impact (p=0.72 and p=0.64, respectively). Conclusions Our findings showed moderate moral distress and low compassion fatigue among oncology nurses. In the examined oncology wards, the prevailing ethical climate was benevolent. Moral distress acts as a mediator between egoistic and benevolence ethical climate and compassion fatigue.